Прогнозирование результатов финансовых инвестиций - Лубенец, Сергей Васильевич; Павленко, Евгений Петрович; Харций, Елена Николаевна (НТУ "ХПИ", 2017)
Предлагаются методы определения ценовых уровней фиксации прибыли и прогнозирования результатов инвестиций на мировых финансовых рынках. Данные методы позволяют выполнять адекватную оценку ряда показателей силы и качества ценовых зон спроса/предложения для поиска наиболее вероятных возможностей для прибыльного инвестирования, прогнозировать размер потенциальной прибыли в каждой отдельной инвестиции, а также определять среднестатистическую доходность торгово-инвестиционной деятельности в целом. Разработаны рекомендации по практическому применением указанных методов с учетом текущей рыночной ситуации.

Methods are offered for determining the price levels for fixing profits in forecasting the results of investments in world financial markets, based on the analysis of price time series taking into account current financial indicators and the market situation. These methods allow an adequate assessment of a number of indicators of strength and quality of the price zones of the supply/demand in order to find the most probable opportunities for profitable investment, it is highly probable to forecast the size of the potential profit in each individual investment, and also to determine the average yield of trade and investment activities in general, taking into account a variety of investment transactions for a long time distance. Recommendations are developed on the practical application of the methods considered taking into account the current market situation. The ways of further researches of the mentioned problems are outlined taking into account the mentioned problem moments.
Forecasting the results of financial investments
Keywords: торгово-инвестиционная деятельность; финансовые рынки; ценовой ряд; прибыль; trade and investment activities; financial markets; price range; profit